Analysis of Factors Influencing Consumer Preferences for Halal Products (A Case Study of Tanjung Morawa Market, Deli Serdang) - M Daffa Raihan Buulolo; Yenni Samri Juliati Nasution; Nur Ahmadi Bi Rahmani (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the effects of halal labels, lifestyle, and income on consumer preferences. A quantitative approach was employed using multiple linear regression analysis. Data were collected through questionnaires from 100 respondents and analyzed using SPSS 25. The validity test indicated that all questionnaire items were valid, with r-count values exceeding the r-table value of 0.196. The reliability test showed that all variables had Cronbach’s Alpha values above 0.60, confirming instrument reliability. The classical assumption tests demonstrated normally distributed data (Monte Carlo Sig. = 0.360 > 0.05), no multicollinearity, and no heteroscedasticity. The regression equation was Y = 7.091 + 0.248X1 + 0.337X2 + 0.111X3. The F-test indicated that halal labels, lifestyle, and income simultaneously affected consumer preferences (Sig. = 0.000 < 0.05). Partially, halal labels (Sig. = 0.002) and lifestyle (Sig. = 0.000) had significant effects, while income had no significant effect (Sig. = 0.114). The R² value of 0.475 indicates that 47.5% of the variation in consumer preferences is explained by the three variables, while 52.5% is attributable to other factors.